Inclusion and Accessibility in Teacher Education - Nijakowska, Joanna; Guz, Ewa (Neofilolog, 2024)
The paper focuses on counteracting discrimination and exclusion in language teacher education by course design which is supportive and inclusive for all students. It also stresses the role of appropriate teacher training in boosting teachers’ sense of preparedness, self-efficacy beliefs and favourable attitudes towards inclusion and accessibility in language education. It promotes inclusive pedagogy (Florian, Black-Hawkins, 2011; Black-Hawkins, Florian, 2012; Florian, Spratt, 2013) and Universal Design for Learning (UDL) (Meyer, Rose, Gordon, 2014; CAST, 2018; Torres, Rao, 2019; Novak, 2022) which allow avoiding stigmatisation and marginalisation of students with diverse needs. The paper uses the SCALED course, developed both for initial teacher education (ITE) and continuing professional development (CPD) of language teachers, as an example of good practice. It provides exemplary solutions which promote effective inclusion by increasing accessibility for students with various needs (including special needs and disabilities) through the universal design the course. The paper presents examples of universal design in relation to the course elements such as the goals, structure, tasks, content, materials, ways of providing feedback and conducting assessment.